2000
DOI: 10.3136/fstr.6.269
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glycolipid Fraction on Fat Bloom in Dark and Milk Chocolates.

Abstract: We earlier reported that glyceroglycolipid extracted from pumpkin significantly retarded the polymorphic transformation from Form V to VI of cocoa butter. We therefore investigated the effects of adding glyceroglycolipid on the fat bloom stability in dark and milk chocolates. Glycolipid fraction containing glyceroglycolipid was extracted with ethanol from pumpkin purée and partially purified on column chromatography. The apparent viscosity of dark and milk chocolates with the addition of the gained glycolipid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Glycolipid fractions from pumpkin have shown anti-bloom properties (Nakae et al, 2000). Sonwai and Rousseau (2006) demonstrated that a cocoa butter equivalent (Coberine®) delayed the onset of bloom in tempered cocoa butter by 1-2 weeks at 25°C.…”
Section: Anti-bloom Compositionmentioning
confidence: 99%
“…Glycolipid fractions from pumpkin have shown anti-bloom properties (Nakae et al, 2000). Sonwai and Rousseau (2006) demonstrated that a cocoa butter equivalent (Coberine®) delayed the onset of bloom in tempered cocoa butter by 1-2 weeks at 25°C.…”
Section: Anti-bloom Compositionmentioning
confidence: 99%
“…Cocoa butter (and chocolate) polymorphism can be influenced by means of additives. It is probably the application that has been investigated the most [3,21,26,29,32,33,58,[75][76][77][78][79][80][81]. In particular the prevention of fat bloom has been targeted [10,38,74,[82][83][84][85][86][87][88].…”
Section: Polymorphism and Melting Profilesmentioning
confidence: 99%
“…3. They prevent the ultimate polymorphic transition that is always associated with chocolate bloom [165].…”
Section: Crystallization Induction Time Savage and Dimickmentioning
confidence: 99%